The Development of Krebet Tourism Village in The Industry 4.0 Era - Desy Nur Aini Fajri (Sekolah Vokasi, Universitas Gadjah Mada, 2020)
The purpose of this study is to explore further how the tourism system of the Krebet Tourism Village in the Industrial Era 4.0. In developing a sustainable tourism village, there must be a tourism system developed to take advantage of opportunities in the Industry 4.0 Era. This study uses a descriptive qualitative research model and in-depth interviews conducted with villager and the local government. The Bantul Regency Government is developing the Krebet Tourism Village so that it can help encourage the growth of the tourism industry in the Province of DIY. Each tourism destination will be influenced by the tourism system which consists of main components that are interrelated in a close and influential relationship. The Gunn Model in the Tourism System - supply and demand can analyze in detail how the tourism system develops the Krebet Tourism Village. The results is to satisfy market demand (Krebet Tourism Village) must be able to provide services and a variety of development (supply) which includes Attractions, Promotions, Information, Services, and Transportation. Besides, the success of the tourism system in the Krebet Village is also influenced by external factors including (1) natural resources; (2) cultural resources; (3) organization/ leadership; (4) financial; (5) labor; (6) entrepreneurship; (7) community; (8) competition; (9) government policies. That is why the Tourism Village must take advantage of opportunities in the industrial era 4.0 by building a good tourism system.